PAREMIAS CONTAINING ONOMASTIC COMPONENTS THAT EXPRESS RELIGIOUS CONCEPTS IN ENGLISH AND UZBEK - Pulatova Muhayyo Azimboyevna (International Journal of Literature and Language Studies, 2026)
This article presents an anthropocentric analysis of paremias containing onomastic components that express religious concepts in English and Uzbek. Drawing on linguocognitive and linguocultural methods, it identifies the similarities and differences between the two languages in this domain.